Dating Carbonaceous Matter in Archean Cherts by Electron Paramagnetic Resonance - Bourbin, M. (Mary Ann Liebert, Inc., 2013)
Ancient geological materials are likely to be contaminated through geological times. Thus, establishing the syngeneity of the organic matter embedded in a mineral matrix is a crucial step in the study of very ancient rocks. This is particularly the case for Archean siliceous sedimentary rocks (cherts), which record the earliest traces of life. We used electron paramagnetic resonance (EPR) for assessing the syngeneity of organic matter in cherts that have a metamorphic grade no higher than greenschist. A correlation between the age of Precambrian samples and the shape of their EPR signal was established and statistically tested. As thermal treatments impact organic matter maturity, the effect of temperature on this syngeneity proxy was studied; cyanobacteria were submitted to cumulative short thermal treatment at high temperatures followed by an analysis of their EPR parameters. The resulting carbonaceous matter showed an evolution similar to that of a thermally treated young chert. Furthermore, the possible effect of metamorphism, which is a longer thermal event at lower temperatures, was ruled out for cherts older than 2 Gyr, based on the study of Silurian cherts of the same age and same precursors but various metamorphic grades. We determined that even the most metamorphosed sample did not exhibit the lineshape of an Archean sample. In the hope of detecting organic contamination in Archean cherts, a “contamination-like” mixture was prepared and studied by EPR. It resulted that the lineshape analysis alone does not allow contamination detection and that it must be performed along with cumulative thermal treatments. Such treatments were applied to three Archean chert samples, making dating of their carbonaceous matter possible. We concluded that EPR is a powerful tool to study primitive organic matter and could be used in further exobiology studies on low-metamorphic grade samples (from Mars for example). Key Words: Kerogen—Sedimentary rocks—Contamination—Spectroscopy—Archean. Astrobiology 13, 151–162.